Antifungal Associations with a Polyelectrolyte Promote Significant Reduction of Minimum Inhibitory Concentrations against Opportunistic Candida spp. Strains - da V Pereira, Lavínia; Rizzi, Tiago; Federizzi, Micaela; Donato, Katarzyna Z; Donato, Ricardo K; Fuentefria, Alexandre M; Reginatto, Paula (Current microbiology, 2024)
The current global scenario presents us with a growing increase in infections caused by fungi, referred to by specialists in the field as a "silent epidemic", aggravated by the limited pharmacological arsenal and increasing resistance to this therapy. For this reason, drug repositioning and therapeutic compound combinations are promising strategies to mitigate this serious problem. In this context, this study investigates the antifungal activity of the non-toxic, low-cost and widely available cationic polyelectrolyte Poly(diallyldimethylammonium chloride) (PDDA), in combination with different antifungal drugs: systemic (amphotericin B, AMB), topical (clioquinol, CLIO) and oral (nitroxoline, NTX). For each combination, different drug:PDDA ratios were tested and, through the broth microdilution technique, the minimum inhibitory concentration (MIC) of these drugs in the different ratios against clinically important Candida species strains was determined. Overall, PDDA combinations with the studied drugs demonstrated a significant increase in drug activity against most strains, reaching MIC reductions of up to 512 fold for the fluconazole resistant Candida krusei (Pichia kudriavzevii). In particular, the AMB-PDDA combination 1:99 was highly effective against AMB-resistant strains, demonstrating the excellent profile of PDDA as an adjuvant/association in novel antifungal formulations with outdated conventional drugs.
Keywords: Amphotericin B; Candidiasis; Antifungal Agents; mikrobiální testy citlivosti; polyelektrolyty; Quaternary Ammonium Compounds; amfotericin B; fungální léková rezistence; lidé; Drug Resistance, Fungal; kvartérní amoniové sloučeniny; Polyethylenes; Microbial Sensitivity Tests; Drug Synergism; synergismus léků; Polyelectrolytes; Candida; Pichia; antifungální látky; polyethyleny; kandidóza; Humans